"Die Dinge stets sich selbst folgen lassen" - Reissig, Elfride (Muzikološki zbornik, 2014)
Music cannot exist without sound, sound can exist without music, therefore sound is more important than music, Giacinto Scelsi's cipher for the cosmos of sound of the single-note, opens a creative space beyond expansion of power and control by improvising and therefore sound itself becomes the mystery.
Keywords: improvizacija; italijanski skladatelji; percepcija; Scelsi, Giacinto, 1905-1988; vzhodna filozofija; zvok